"JUSTICE AND MORALITY IN ’TO KILL A MOCKINGBIRD’" - Umida Abdushukurova (Scientific Impulse, 2024)
Harper Lee's timeless novel, "To Kill a Mockingbird," continues to captivate readers with its poignant exploration of justice and morality in the Deep South. This abstract aims to provide a comprehensive overview of the themes of justice and morality as portrayed in the novel. Through an analysis of key characters, plot points, and societal dynamics, this abstract delves into the complexities of racial injustice, moral integrity, and the struggle for truth in the face of prejudice. The abstract begins with an introduction to the novel's setting in the racially divided town of Maycomb, Alabama, during the 1930s. It then explores the central theme of racial injustice, focusing on the trial of Tom Robinson and the failure of the legal system to deliver true justice in the face of deep-seated prejudice. Through the character of Atticus Finch, the abstract examines the moral compass that guides the narrative, highlighting his unwavering commitment to truth and fairness despite the societal pressures he faces. Furthermore, the abstract discusses the role of children, particularly Scout and Jem Finch, in navigating the complexities of morality and empathy in a flawed society. It also explores the influence of social class on perceptions of justice and morality, as well as the significance of symbols and metaphors in conveying deeper moral truths. In addition to analyzing the novel's themes within its historical context, this abstract also considers its relevance to contemporary society. By examining issues of racism, prejudice, and social justice, it underscores the enduring significance of "To Kill a Mockingbird" as a powerful commentary on the human condition and the quest for moral righteousness in the face of adversity.